Memoirs of the oil industry in Burma (905 A.D. - 1980 A.D.) : . Memoirs of oil industry in Burma (905 A.D. - 1980 A.D.) (Pagan U Khin Maung Gyi, 1989)
Cover title: Memoirs of oil industry in Burma (905 A.D - 1980 A.D.).